Analysis of home education historical roots in the world and in Poland - Maria Racewicz (Rozprawy Społeczne)
Introduction The article presents the results of research on the analysis of the home education development over the centuries. Particular emphasis has been placed on the development of this form of education in Poland in recent years. It also mentions the importance of teaching in the home environment as a method of natural and child-friendly acquisition of knowledge about the world and the transmission of moral values professed by parents.